Gen ZY Customers and Trendy Restaurants in Metropolitan City: A Measurement of Price Fairness, Sensory Experience, and Satisfaction - Christian, Michael; Jonathan, Ivan; Indriyarti, Eko Retno (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2024)
The food and beverage sector in Indonesia is becoming increasingly competitive, particularly in restaurants with current themes. Several restaurants were quite enthusiastic about adding outlets during the first opening phase, but they were forced to close one by one over time. In this situation, satisfaction and loyalty can decide the restaurant's long-term viability. Based on this, this study was undertaken with the goal of studying the determinants of modern restaurant customer loyalty utilizing price fairness, sensory experience, and customer satisfaction as predictive variables. This quantitative study employs partial lease square structural equation modeling (PLS-SEM) with Smart PLS 4.0 as an analytical tool. The findings of this study, which used purposive sampling on 190 Warunk Upnormal consumers ranging in age from generations Z to Y, demonstrate how pricing fairness and sensory experience influence happiness and loyalty. Similarly, satisfaction influences consumer loyalty. This study reveals that restaurants with a contemporary concept have key characteristics in terms of facilities that are appealing to look at and enjoy, such as the aroma of their food. However, if the target clientele for restaurants with contemporary themes are young people, the issue of pricing fairness must be addressed.